Caste, gender and class in panchayats: case of barddhaman, West-Bengal - Liieten, G.K.
Accourding to the author a truly emancipatory movement requires continuous political and social action leading to enforcement. It high lights an aspect of enforcement by examining closely the functioning of the panchayat institution in West Bengal. Empirical material from one black in the district of bardhaman is the primary reference and additional material from a block in Birbhum in the secondary reference.
Keywords: Village Panchayats; Panchayati Raj; Caste; Village Panchayats - India - West Bengal